Role of inflammation, immunity, and oxidative stress in hypertension: New insights and potential therapeutic targets - Zhang, Zenglei; Zhao, Lin; Zhou, Xingyu; Meng, Xu; Zhou, Xianliang (Frontiers in Immunology, 2023)
Hypertension is regarded as the most prominent risk factor for cardiovascular diseases, which have become a primary cause of death, and recent research has demonstrated that chronic inflammation is involved in the pathogenesis of hypertension. Both innate and adaptive immunity are now known to promote the elevation of blood pressure by triggering vascular inflammation and microvascular remodeling. For example, as an important part of innate immune system, classically activated macrophages (M1), neutrophils, and dendritic cells contribute to hypertension by secreting inflammatory cytokines. In particular, interferon-gamma (IFN-γ) and interleukin-17 (IL-17) produced by activated T lymphocytes contribute to hypertension by inducing oxidative stress injury and endothelial dysfunction. However, the regulatory T cells and alternatively activated macrophages (M2) may have a protective role in hypertension. Although inflammation is related to hypertension, the exact mechanisms are complex and unclear. The present review aims to reveal the roles of inflammation, immunity, and oxidative stress in the initiation and evolution of hypertension. We envisage that the review will strengthen public understanding of the pathophysiological mechanisms of hypertension and may provide new insights and potential therapeutic strategies for hypertension.